2011
DOI: 10.1111/j.1875-595x.2011.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial to assess maintenance of gingival health by a novel dentifrice containing 0.1%w/w o-cymen-5-ol and 0.6%w/w zinc chloride

Abstract: A randomised clinical trial to assess maintenance of gingival health by a novel dentifrice containing 0.1%w⁄w o-cymen-5-ol and 0.6%w⁄w zinc chloride Objectives: To assess the ability of 0.1%w ⁄ w o-cymen-5-ol ⁄ 0.6%w ⁄ w zinc chloride dentifrice to maintain gingival health compared to a sodium fluoride control dentifrice. Design: Following a baseline examination, subjects went through a regimen to bring them to a high level of gingival health. This included a professional prophylaxis supported by oral hygiene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…These results indicate that this antimicrobial activity of the formulation as reported by Pizzey 2 does control dental plaque and enhance the ability of the gel to foam dentifrice to maintain gingival health over the 12 week test period compared to a regular sodium fluoride dentifrice. The results from this study show similar benefits in maintenance of gingival health for an 0.1%w/w o‐cymen‐5‐ol/ 0.6%w/w zinc chloride dentifrice in a gel to foam format as those observed for a 0.1%w/w / 0.6%w/w zinc chloride dentifrice 1 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These results indicate that this antimicrobial activity of the formulation as reported by Pizzey 2 does control dental plaque and enhance the ability of the gel to foam dentifrice to maintain gingival health over the 12 week test period compared to a regular sodium fluoride dentifrice. The results from this study show similar benefits in maintenance of gingival health for an 0.1%w/w o‐cymen‐5‐ol/ 0.6%w/w zinc chloride dentifrice in a gel to foam format as those observed for a 0.1%w/w / 0.6%w/w zinc chloride dentifrice 1 .…”
Section: Discussionsupporting
confidence: 68%
“…This clinical study is a second clinical investigation to assess the ability of a dentifrice containing 0.1%w/w o‐cymen‐5‐ol and 0.6%w/w zinc chloride to maintain gingival health following a 14 day pre‐experimental phase of dental prophylaxis and oral hygiene instruction prior to study treatment compared to a regular sodium fluoride/ silica based dentifrice. The first clinical study 1 evaluated a paste dentifrice containing 0.1%w/w o‐cymen‐5‐ol and 0.6%w/w zinc chloride, while this clinical investigation evaluates a similar formulation in a gel to foam format. The gel to foam format contains an elevated surfactant level and generates greater foam volume compared to the control dentifrice through evaporation of the post‐foaming agent, isopentane.…”
mentioning
confidence: 99%
“…These dentifrices have been tested in two clinical studies reported in this issue by Kakar et al 17,18 , but unlike the studies of Svatun and Saxton 11,12 the group of subjects enrolled in these studies represent a greater age range and are more diverse. The Kakar studies in this issue 17,18 describe the use of a standard dentifrice 16 , and a gel to foam dentifrice 18 containing 0.1%w/w o‐cymen‐5‐ol and 0.6%w/w zinc chloride to maintain gingival health following a pre‐experimental phase of dental prophylaxis and oral hygiene instruction prior to study treatment compared to a regular sodium fluoride/ silica based dentifrice control. The pre‐experimental phase brought subjects to their optimum gingival health prior to commencing study treatment and achieved significant reductions between the pre‐prophylaxis visit and the treatment commencement visit of 76.8% reduction in MGI, and a reduction of 69.4% in BI 16 or 84.7% reduction in MGI, 66.2% reduction in BI 17 ( P < 0.0001 in both cases).…”
Section: Current Product Science and Testingmentioning
confidence: 99%
“…The Kakar studies in this issue 17,18 describe the use of a standard dentifrice 16 , and a gel to foam dentifrice 18 containing 0.1%w/w o‐cymen‐5‐ol and 0.6%w/w zinc chloride to maintain gingival health following a pre‐experimental phase of dental prophylaxis and oral hygiene instruction prior to study treatment compared to a regular sodium fluoride/ silica based dentifrice control. The pre‐experimental phase brought subjects to their optimum gingival health prior to commencing study treatment and achieved significant reductions between the pre‐prophylaxis visit and the treatment commencement visit of 76.8% reduction in MGI, and a reduction of 69.4% in BI 16 or 84.7% reduction in MGI, 66.2% reduction in BI 17 ( P < 0.0001 in both cases). While Kakar et al 17,18 also report the mean gingival index following the use of this experimental dentifrice as is traditionally reported, Butler et al 19 reports a statistical approach which increases the ability to understand what this means in the treatment of patients on an everyday basis.…”
Section: Current Product Science and Testingmentioning
confidence: 99%
See 1 more Smart Citation